2009
DOI: 10.1093/aje/kwn414
|View full text |Cite
|
Sign up to set email alerts
|

Serum Selenium and Peripheral Arterial Disease: Results From the National Health and Nutrition Examination Survey, 2003-2004

Abstract: The authors conducted a cross-sectional study of the association of serum selenium with the prevalence of peripheral arterial disease among 2,062 US men and women 40 years of age or older participating in the National Health and Nutrition Examination Survey, 2003-2004. Serum selenium was measured by using inductively coupled plasma-dynamic reaction cell-mass spectrometry. Peripheral arterial disease was defined as an ankle-brachial blood pressure index <0.90. The age-, sex-, and race-adjusted prevalence of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 47 publications
3
45
2
2
Order By: Relevance
“…Our result is in opposition with most European surveys (Arnaud et al, 2006;Meplan et al, 2007;Ortega et al, 2012) or US populations (Bleys et al, 2009), in which obese patients have lower serum selenium concentration, but in agreement with Dewailly's survey of a French Polynesian sampling in which selenium concentration in blood was positively linked to BMI , the regression coefficient (β) being 0.02, i.e. ten times higher than in our study, among the controls (β=0.002).…”
Section: Discussioncontrasting
confidence: 65%
“…Our result is in opposition with most European surveys (Arnaud et al, 2006;Meplan et al, 2007;Ortega et al, 2012) or US populations (Bleys et al, 2009), in which obese patients have lower serum selenium concentration, but in agreement with Dewailly's survey of a French Polynesian sampling in which selenium concentration in blood was positively linked to BMI , the regression coefficient (β) being 0.02, i.e. ten times higher than in our study, among the controls (β=0.002).…”
Section: Discussioncontrasting
confidence: 65%
“…50 However, recent observational evidence in selenium-replete populations such as that of the US is suggestive of a possible U-shaped association (Figure 1) between selenium status and CVD. [48][49] Results from randomized trials of selenium supplementation do not support a role for selenium in cardiovascular prevention at the present time. …”
Section: Selenium and Cardiovascular Diseasementioning
confidence: 86%
“…[43][44][45][46][47][48][49] Inverse associations have been found particularly in populations with relatively low selenium intake or status. [43][44][45][46][47] For instance, in a German population of 636 patients with suspected coronary artery disease, mean plasma selenium was 69.5 and 74.5 µg/L at baseline in patients with and without a recurring cardiovascular event, respectively.…”
Section: Selenium and Cardiovascular Diseasementioning
confidence: 99%
“…The association between ischemic heart disease and selenium has been reported in several studies (8)(9)(10). Salonen et al observed a 2.9-fold increased risk of cardiovascular death in patients with low selenium levels (11) However, the efficacy of selenium supplementation as a single dietary additive has been debated (8)(9)(10)12). Absence of clinical effects may, in some cases, be explained by short-term intervention periods and/or low selenoprotein activity due to concomitant coenzyme Q10 deficiency, a nutrient necessary for selenoprotein synthesis (13).…”
Section: Introductionmentioning
confidence: 88%
“…have proposed that selenium affects tumour development (7). The association between ischemic heart disease and selenium has been reported in several studies (8)(9)(10). Salonen et al observed a 2.9-fold increased risk of cardiovascular death in patients with low selenium levels (11) However, the efficacy of selenium supplementation as a single dietary additive has been debated (8)(9)(10)12).…”
Section: Introductionmentioning
confidence: 99%